2011
DOI: 10.1136/bcr.03.2011.4013
|View full text |Cite
|
Sign up to set email alerts
|

Primary liposarcoma of the heart

Abstract: The author reports a case of a 64-year-old man, who presented with a 4-week history of dyspnoea and dizziness suffering from a large mass in the pericardium. CT of the chest showed a lobulated mass in the pericardial sac located between the pulmonary veins and the ascending aorta reaching the superior vena cava. The tumour was completely resected and histopathological analysis revealed the tumour to be a well-differentiated lipoma-like and focal sclerosing liposarcoma, which was composed predominantly of adipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Unlike well‐differentiated liposarcoma, which retains lipotomatous features, DDLPS is a nonlipotomatous highly cellular malignancy with a much more aggressive phenotype with a high rate of local recurrence and systemic metastases . On the basis of previous studies, supernumerary rings and/or giant rod chromosomes in the 12q13‐15 region of DDLPS have been detected.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike well‐differentiated liposarcoma, which retains lipotomatous features, DDLPS is a nonlipotomatous highly cellular malignancy with a much more aggressive phenotype with a high rate of local recurrence and systemic metastases . On the basis of previous studies, supernumerary rings and/or giant rod chromosomes in the 12q13‐15 region of DDLPS have been detected.…”
Section: Discussionmentioning
confidence: 99%
“…The most common soft tissue sarcoma subtypes in adults include undifferentiated/unclassified soft tissue sarcoma, undifferentiated pleomorphic sarcoma, liposarcoma, leiomyosarcoma, and gastrointestinal stromal tumors (GIST). Liposarcoma constitutes only 13% of all cardiac sarcomas, arises from adipocytes, and has three main morphologic subgroups that vary in their metastatic potential according to 2013 WHO classification of soft tissue sarcoma: (1) myxoid, (2) dedifferentiated, and (3) pleomorphic liposarcoma [ 7 ]. Myxoid liposarcoma are low-grade tumors while dedifferentiated and pleomorphic liposarcomas are highly aggressive tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The study also reported that complete tumor resection and adjuvant radiation therapy contributed to the reduced risk of local recurrence and metastasis. Specifically with liposarcoma, recurrence was seen in approximately 40% of the cases and was reported to be up to 14 years after the initial surgical resection [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite liposarcoma being the most common cancer of mesenchymal origin in adults, 75% of liposarcoma cases occur in deep muscle tissue of the limbs, 20% occur in the retroperitoneum, and the remainder occur in other sites. Mediastinal liposarcoma is extremely rare ( 5 , 6 ); primary mediastinal liposarcoma accounts for only 0.13–0.75% of mediastinal cancers, and most occur in the posterior mediastinum ( 6 ). Cardiac liposarcoma is even rarer and account for approximately 1% of all primary cardiac malignant tumours ( 2 , 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%